Building broad-based partnership for sustainable forest management: the Model Forest experience in Cameroon - Jum, C.N.; Nguiebouri, J.; Zoa, M.; Diaw, C. (2007)
The humid forest zone of Cameroon is part of the biodiversity rich Congo Basin. Until the mid-1990s, the forests of Cameroon were centrally managed, which excluded communities from accessing forest resources and gaining economic benefits from them. In the early 1990s, more participative forest management practices emerged. The new forestry legislation of 1994 – focusing on the devolution of management responsibilities to local communities – has reinforced this participatory trend. In 2003, the Center for International Forestry Research (CIFOR) and its partners started the Model Forest Project in Cameroon. This project is part of the International Model Forest Network (IMFN). The goal of the IMFN is the sustainable management of forests around the world, while taking into account the needs of local communities. This paper describes the process that led the Cameroonian Government to the recognition, in 2005, of Campo-Ma’an and Dja et Mpomo as Model Forest sites. It gives a description of the sites, the partnerships involved, stakeholders’ perspectives, the accomplishments to date and future perspectives. It concludes that, while the project provides a framework for reflection, innovation and collective learning, it is as yet too early to demonstrate concrete progress or results.